Exploring Lactic Acid Bacteria and Metabolite-Target Interactions in Undernutrition Prevention: A Network Pharmacology and Molecular Docking Approach - Prayogi, Norbertus Marcell; Berawi, Khairun Nisa; Irawati, Nur Ayu Virginia; Rukmono, Prambudi (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Undernutrition is a major global issue, particularly in children, leading to stunting, wasting, and compromised immune function. Disruption of gut microbiota is a key factor in undernutrition, making probiotics, especially Lactic Acid Bacteria (LAB), a potential solution for improving nutritional status. This study explores the role of LAB and their metabolites in preventing undernutrition using network pharmacology and molecular docking approaches to identify potential molecular targets and related pathways. Network pharmacology tools like TargetNet, SEA, and SwissTargetPrediction were used to predict gene targets influenced by LAB metabolites. Cytoscape was used to build protein-protein interaction (PPI) networks, and molecular docking simulations evaluated the binding of LAB metabolites to key proteins associated with undernutrition. A total of 603 potential genes were identified, including human serum albumin (ALB), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α). Pathway analysis linked these proteins to immune response, nutrient absorption, and metabolic regulation. Molecular docking confirmed stable interactions with LAB metabolites. LAB and their metabolites show promise in managing undernutrition by modulating gut health and supporting nutrient absorption, providing a basis for future clinical applications. Keywords: Undernutrition, Lactic Acid Bacteria (LAB), Probiotics, Network Pharmacology, Molecular Docking